A role for social media? A community‐based response to guns, gangs, and violence online. Issue 3 (16th August 2020) - Sichel, Corianna E.; Javdani, Shabnam; Shaw, Stephanie; Liggett, Roberta
Abstract: Social media represents a relatively novel environment for prevention efforts targeting youth gun and gang violence, and associated trauma. The aim of this study is, therefore, to present findings from a novel intervention designed to complement existing, community‐based violence prevention efforts. In doing so, we focus on the role of adult empathy in the relationships between youth and the adult credible messengers (CMs) who deliver the program. Guided by the purpose of complementarity, our mixed methods data analyses combine insights gained from CM's quantitative reports of 145 instances of risky online behavior with qualitative analyses of three focus groups addressing their experiences. Results underscore the complexities of social media as a context with the potential to simultaneously contribute to, and serve to prevent, trauma. Results also indicate that empathic concern and perspective taking were important in informing the type of intervention tactics employed by CMs. Relatedly, CM's perspective taking mattered not only in their responses to risky and/or trauma‐related content, but also in their identification of some relevant social media posts.